2019
DOI: 10.15561/18189172.2019.0401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of self-reliance of athletes of different sports

Abstract: The purpose of the study is to identify self-reliance manifestation features among qualified athletes of different sports. Material and methods. The study participants were representatives of combat sports (boxing) n = 23, complex-coordination (gymnastics) n = 25, speed-strength (discus throw) n = 23, and also cyclic sports (swimming) n = 38. In total 109 sportsmen. The age of the respondents was from 16 to 18 years old. Comprehensive psycho-diagnostic methods diagnose self-reliance level and manifestation deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…The fourth factor in this research was player personality, which refers to self-reliance, strong mentality, responsibility, and relentlessness, valuable personality traits in today's competitive football world. For example, self-reliance is the primary ingredient of self-confidence, which is essential for the athlete to move forward from loss and despair (Kolosov et al, 2019;Martínez Lorca et al, 2023). Dominado (2018) found that the loss of self-belief or selfresilience influences the athlete's perception of the emotional aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth factor in this research was player personality, which refers to self-reliance, strong mentality, responsibility, and relentlessness, valuable personality traits in today's competitive football world. For example, self-reliance is the primary ingredient of self-confidence, which is essential for the athlete to move forward from loss and despair (Kolosov et al, 2019;Martínez Lorca et al, 2023). Dominado (2018) found that the loss of self-belief or selfresilience influences the athlete's perception of the emotional aspect.…”
Section: Discussionmentioning
confidence: 99%
“…В исследованиях самореализации спортсменов ее обычно изучают, опираясь не на психологические показатели, а на наличие либо определенной спортивной квалификации, либо исходя из участия спортсменов в международных соревнованиях и показанных на них результатах (Уляева et al, 2021;Kolosov et al, 2019). Мы в исследовании подошли к вопросу самореализации с системной точки зрения, что позволило нам рассмотреть компоненты и виды самореализации (Кудинов, 2012;Rusu, 2019).…”
Section: Discussionunclassified
“…Тем не менее восхождение к выдающимся результат в спорте невозможно без систематической, продуманной психологической подготовки, направленной на формирование личности спортсмена. Это обеспечивает успех и устойчивость соревновательной деятельности, максимальную реализации потенциала спортсмена [3,5].…”
Section: Introductionunclassified